2019
DOI: 10.1021/acs.jpcc.9b04784
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Stacking Effects of Bilayer MoSSe on Photocatalytic Water Splitting

Abstract: Stacking two-dimensional materials into a heterostructure, which is also known as van der Waals epitaxy, is an effective method to tune the properties of pristine monolayer structures. Recently, Janus monolayer MoSSe has been successfully fabricated in an experiment, which might be beneficial for photocatalytic water splitting due to the inner electric field caused by the breaking of the inversion symmetry. Considering that the bilayer structure has natural advantages over the monolayer structure in photocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…For the recently emerged Janus MoSSe layered materials, it has been theoretically predicted that, stacking the monolayers to form bilayers could effectively narrow the band gap [ 11 , 12 ], causing a reinforced optical absorption, which is similar to the cases of C 3 N 4 and PtSSe [ 13 , 14 ]. In the meantime, the dipole moment of Janus MoSSe layered materials, which is represented by the plane electrostatic potential difference between the two surfaces, has been found to almost linearly increase with the growing thickness [ 11 , 12 , 15 ]. Furthermore, the observed type-II band alignment in the Janus MoSSe bilayers could suppress the recombination of photo-excited carriers for the thorough-going spatial separation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the recently emerged Janus MoSSe layered materials, it has been theoretically predicted that, stacking the monolayers to form bilayers could effectively narrow the band gap [ 11 , 12 ], causing a reinforced optical absorption, which is similar to the cases of C 3 N 4 and PtSSe [ 13 , 14 ]. In the meantime, the dipole moment of Janus MoSSe layered materials, which is represented by the plane electrostatic potential difference between the two surfaces, has been found to almost linearly increase with the growing thickness [ 11 , 12 , 15 ]. Furthermore, the observed type-II band alignment in the Janus MoSSe bilayers could suppress the recombination of photo-excited carriers for the thorough-going spatial separation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the electronic properties of nanomaterials can be well adjusted by external stimuli, it has been found that tensile strain and transition metal atom adsorption could strengthen optical absorption [9,29]. More interestingly, in 2D Janus MoSSe BL, the light absorption can be improved effectively by changing the stacking configurations [10,11,15].…”
Section: Utilization Of Sunlightmentioning
confidence: 99%
“…This will substantially enhance the light utilization efficiency. Motivated by these beneficial properties, a large number of 2D Janus single layers (SLs) and bilayers (BLs) have been designed for the application of photocatalytic water splitting, such as III 2 XY (III = Ga and In; X, Y = S, Se, and Te, and X ̸ = Y) SLs [7,8], MXY (M = Mo, W) SL and BL [9][10][11][12][13], ScXY SLs [14], PtSSe SL and BL [15], and MXZ (M = Zr, and Hf; X = S and Se; Z = O and S; X ̸ = Z) SLs [16]. Based on the reaction mechanism, photocatalytic water splitting can be divided into four steps (see figure 1(b)): (1) adsorption of water molecules, (2) utilization of sunlight, (3) charge separation and transport, and (4) surface hydrogen evolution reaction (HER) and oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%
“…[92] In fact, it has been widely proven that heterojunction photocatalysts can promote the spatial separation of photogenerated electron hole pairs, to achieve higher overall photocatalytic activity. [93][94][95] Qin et al designed a 2D ZnInS 4 /g-C 3 N 4 vdWh with S vacancy photocatalyst for hydrogen evolution (see Figure 9a). [96] The optimized S vacancy ZnInS 4 /g-C 3 N 4 vdWh has a hydrogen production efficiency of 6095.1 µmol h −1 g −1 .…”
Section: Photocatalysismentioning
confidence: 99%